2010
DOI: 10.1159/000321514
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Control of Estrogen Receptor Expression and Tumor Suppressor Genes Is Modulated by Bioactive Food Compounds

Abstract: Background: The tumor suppressor genes p15INK4b and p16INK4a as well as the estrogen receptor-α (ESR1) gene are abnormally methylated and expressed in colon cancer. The cancer-preventative abilities of several bioactive food components have been linked to their estrogenic and epigenetic activities. Methods: The effect of folic acid, zebularine, resveratrol, genistein and epigallocatechin-3-gallate (EGCG) on tumor cell growth, promoter methylation of ESR1, p15INK4b and p16I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 82 publications
0
30
0
1
Order By: Relevance
“…Reactivation of some methylation-silenced genes by EGCG has also been demonstrated in human colon cancer HT-29 cells, esophageal cancer KYSE 150 cells and prostate cancer PC3 cells [26,27]. Berner et al [31] have shown that EGCG treatment suppressed promoter methylation of tumor suppressor genes p15 INK4b and p16 INK4a in Caco2 cells [31]. Gao et al [32] have demonstrated that EGCG reverses promoter methylation of tumor suppressor WIF-1 and restores WIF-1 expression in H460 and A549 lung cancer cells [32].…”
Section: Resultsmentioning
confidence: 99%
“…Reactivation of some methylation-silenced genes by EGCG has also been demonstrated in human colon cancer HT-29 cells, esophageal cancer KYSE 150 cells and prostate cancer PC3 cells [26,27]. Berner et al [31] have shown that EGCG treatment suppressed promoter methylation of tumor suppressor genes p15 INK4b and p16 INK4a in Caco2 cells [31]. Gao et al [32] have demonstrated that EGCG reverses promoter methylation of tumor suppressor WIF-1 and restores WIF-1 expression in H460 and A549 lung cancer cells [32].…”
Section: Resultsmentioning
confidence: 99%
“…The cancer-preventive abilities of several bioactive food components, including resveratrol, genistein, and EGCG, have been linked also to their ability to regulate tumor suppressor gene expression by epigenetic processes [44]. Our data showed that Ind altered global DNA methylation and induced the demethylation of specific gene promoters, with effects depending on the specific cell line investigated, indicating different sensitivities of different cell lines to the phytochemical.…”
Section: Discussionmentioning
confidence: 78%
“…By decreasing DNA methylation and elevating histone acetylation, EGCG treatment induced the reexpression of silenced tumor suppressor genes, p16 and p21, in human skin cancer cells (Nandakumar et al 2011 ). In colon cancer cells, EGCG restored the expression of tumor suppressive p15 and p16 by decreasing their promoter methylation, and repressed colon cancer cell proliferation (Berner et al 2010 ). In addition to regulating DNMTs and causing direct changes in DNA methylation, EGCG has been reported to impact the level of S -adenosylmethionine (SAM), the universal methyl donor, thereby indirectly mediating DNA methylation (Park et al 2012 ).…”
Section: Food Components That Inhibit Cancer Cell Growthmentioning
confidence: 98%